MEANS OF EXPRESSION USING PROVERBS AND SAYINGS IN RUSSIAN LANGUAGE LESSONS, IN SCHOOLS WITH THE UZBEK LANGUAGE OF INSTRUCTION - U. E. Ataev (Galaxy International Interdisciplinary Research Journal, 2023)
One of the difficult tasks is the ability to use and understand Russian proverbs and sayings in speech, for Uzbek schoolchildren. This article shows some ways of using proverbs and sayings in teaching Russian in schools with Uzbek language of instruction.